Assessing the Current Situation and Economic Feasibility of Eco-Friendly Materials: Example from Thakurgaon, Bangladesh - Shahen, Md. Abu (Indonesian Journal of Community Services, 2025)
In contrast to traditional bricks, the study investigated the propensity of microentrepreneurs to use and conduct business with eco-friendly building products. Through key informant interviews and focus groups, we investigated the inclination to choose eco-friendly materials. A total of one hundred microentrepreneurs were surveyed, and eight key interviews and four group discussions were conducted in the research region. However, the data revealed that only a small percentage of microentrepreneurs have a basic awareness of pollution and environmental issues. A sizable fraction of the MEs were unable to successfully adopt waste management. Additionally, the survey found that a minimal percentage of MEs use environmentally friendly production and marketing techniques. For the production of traditionally fired bricks, dirt was the main ingredient in all brick kilns, which used firewood as fuel. They were not skilled enough to use fly ash as a raw material to make bricks and other building supplies. Furthermore, the participation rate of women in these enterprises was incredibly low, and their remuneration was extremely inadequate. Businesses should place a high priority on fostering a positive work environment for women and enacting fair wage laws that increase the pay of female employees. A sizable fraction of the microentrepreneurs (MEs) did not follow proper safety procedures and lacked training. Therefore, microbusiness owners should organize safety- and security-focused training for themselves as well as for employees.